Sociolinguistic Perception and Evaluation in 19th-Century Texts from Peru - Caravedo, Rocío (2025)
From a sociocognitive view, we intend to analyze and explain the perception and evaluation of linguistic phenomena from this period, in contrast with modern Spanish. We base our analysis on journalistic texts, some published in Museo de Limeñadas by Ramón Rojas y Cañas (1853) and on the costumbrist volume Lima by Manuel Atanasio Fuentes (Paris, 1867). This study offers a sociolinguistic diachronic perspective on linguistic diversity in Peru, a few decades after the independence from Spain.